2015
DOI: 10.1111/jfpe.12217
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound as a Pretreatment Method to Improve Drying Kinetics and Sensory Properties of Dried Apple

Abstract: The effect of ultrasound pretreatment on drying kinetics and physical properties as color and rehydration rate of dried apple slices was investigated. Apple samples var. Idared were submitted to ultrasonic treatment using 21 and 35 kHz for 30 min in an ultrasound bath securing sound intensity of 3 and 4 W/cm 2 , respectively. After pretreatment, the material was dried in a convective oven at 70C and at an air velocity of 2 m/s. The sonication reduced drying time by 13-17% in comparison with the untreated sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
84
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 36 publications
11
84
0
1
Order By: Relevance
“…This effect was noticed by Prinzivalli, Brambilla, Maffi, Lo Scalzo, and Torreggiani (2006) in strawberry slices. As reported in the literature in the case of dehydrated apples and carrots, the pre-treatment with ultrasound leads to an increase in lightness (L*) compared to the untreated fruit (Fijalkowska, Nowacka, Wiktor, Sledz, & Witrowa-Rajchert, 2016). In our case, significantly higher values of L* for untreated and US treated samples were observed only at the 8th week of storage.…”
mentioning
confidence: 72%
“…This effect was noticed by Prinzivalli, Brambilla, Maffi, Lo Scalzo, and Torreggiani (2006) in strawberry slices. As reported in the literature in the case of dehydrated apples and carrots, the pre-treatment with ultrasound leads to an increase in lightness (L*) compared to the untreated fruit (Fijalkowska, Nowacka, Wiktor, Sledz, & Witrowa-Rajchert, 2016). In our case, significantly higher values of L* for untreated and US treated samples were observed only at the 8th week of storage.…”
mentioning
confidence: 72%
“…The effective moisture diffusion coefficient can be considered as a parameter that characterizes the drying rate [17,32]. The highest value of this parameter equalled to 5.00 Á 10 À10 m 2 /s and it was observed for untreated sample.…”
Section: Characteristics Of Drying Processmentioning
confidence: 99%
“…The effective water diffusion coefficient (D eff ) was calculated using TableCurve 2D v5.01 software on the basis of the simplified Fick's diffusion equation [32]: [33].…”
Section: Drying Processmentioning
confidence: 99%
“…Ultrasound treatment can decrease the drying time and increase the quality of dried samples [21,30,31]. So, ultrasound was applied to treat Feizixiao lychee pulp in order to improve the appearance of FD pulp.…”
Section: Effect Of Ultrasound On Fd Feizixiao Lycheementioning
confidence: 99%
“…It indicated that ultrasound pretreatment prior to freeze-drying can improve the efficiency of FD and the stability during storage of FD pear. Ultrasound pretreatment did reduce drying time by 13-17%, increased the lightness, decreased the brown pulp, and improved the rehydration properties of dried apple [21].…”
Section: Introductionmentioning
confidence: 99%